2005
DOI: 10.1002/cphc.200400598
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Poly(ε‐lysine)‐Grafted Dextrans and Their pH‐ and Thermosensitive Hydrogelation with Cyclodextrins

Abstract: To give pH sensitivity to a thermoreversible supramolecular-structured hydrogel system, poly(epsilon-lysine) (PL), as a cationic polymer, was grafted to dextran and used for inclusion complexation with alpha-cyclodextrins (alpha-CDs). The synthesized graft copolymer was characterized by 1H NMR spectroscopy, and the hydrogel formation was confirmed by X-ray diffraction and solid-state 13C NMR analysis. The hydrogelation was induced from a phase-separated structure of hydrated dextrans and hydrophobically aggreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 38 publications
(13 reference statements)
1
43
0
Order By: Relevance
“…The hydrophobic interactions within the networks confer long‐term sustained release of various drug molecules, proteins, and amino acids where loading of the payload could be implemented under mild conditions (i.e., physiological pH and room temperature) and prior to gelation, which is particularly advantageous in the field of tissue engineering. In addition to thermo‐responsiveness, pH‐, photo‐, and redox‐responsiveness have also been incorporated into these systems by careful selection of the polymers. Although these systems may serve as scaffolds for sustained release systems, their true potential is yet to be realized, with many reports still in the in vitro stage using (model) drugs and proteins .…”
Section: Cyclodextrin‐based Hydrogel Networkmentioning
confidence: 99%
“…The hydrophobic interactions within the networks confer long‐term sustained release of various drug molecules, proteins, and amino acids where loading of the payload could be implemented under mild conditions (i.e., physiological pH and room temperature) and prior to gelation, which is particularly advantageous in the field of tissue engineering. In addition to thermo‐responsiveness, pH‐, photo‐, and redox‐responsiveness have also been incorporated into these systems by careful selection of the polymers. Although these systems may serve as scaffolds for sustained release systems, their true potential is yet to be realized, with many reports still in the in vitro stage using (model) drugs and proteins .…”
Section: Cyclodextrin‐based Hydrogel Networkmentioning
confidence: 99%
“…The protonation degree of the amine groups of ε‐PL (p K a ≈ 9.0)55, 56 was adjusted with concentrated HCl from a naturally basic condition (pH 8.5), to neutral, and acidic (pH 4). With ε‐PL at pH 8.5, its protonation degree was expected to be very slightly, and ζ of the β‐carotene nanoparticles increased from −20 to −8 mV (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…109,110 In an attempt to produce stiffer CD-PPRTX hydrogels, while decreasing the total weight concentrations of the starting components, the researchers also used interpeptide hydrogen bonding as an additional associative force. 111,112 For example, Dong et al demonstrated that usage of diblock copolymers containing PEG with molecular weight around 5 kDa and biodegradable polypeptide poly(L-glutamic acid) (PLG) leads to aCD-PPRTX hydrogels with remarkably high elastic storage modulus (G 0~1 0 4 Pa at 10 wt% vs. 10 3 Pa at 15 wt% for conventional amphiphilic hydrogels) and long-loaded doxorubicin release times. 111 This gel strengthening phenomenon was ascribed to extra hydrogen bonding between the PLG blocks under acidic pH and its synergy with polypseudorotaxane hydrogen bond-driven associations.…”
Section: Hierarchical Hydrogels Formed From Cyclodextrin-based Polypsmentioning
confidence: 98%